Training of health profesionals for Primary Health Care - Salcedo-Espinoza, Carlos (2022)
This article analyzes the important relationship between the process of training students in health-related professions and primary health care. It touches on the conceptual points of primary care and the current characteristics of university training processes, as well as suggestions for actions to be taken to improve this relationship in the academic aspect. It touches on the relevance of the establishment of general studies as the main headquarters that will improve professionalization and, therefore, adequate medical care.